The development and validation of student career planning inventory (SCPI) - Wulandari, Arifah; Rahman, Diniy Hidayatur; Hambali, IM (ProGCouns: Journal of Professionals in Guidance and Counseling, 2023)
The fluctuating, dynamic and unpredictable development of the work setting Emphasizes the significance of career planning. However, there is still no measurement tool for planning skills based on career construction theory. The objective of this research is to develop and validate an inventory that can measure the level of students' career planning skills based on career construction theory. This research used the ADDIE research design with five development stages including analysis, design, development, implementation, and evaluation. The resulting items amounted to 29 statement items developed from three indicators that are crystallization of vocational preferences, specification of occupational choice and actualization of occupational choice. 112 vocational students were involved in the process of analyzing the instrument validity and reliability. The results of the analysis with the Pearson Product Moment Correlation test resulted in an r-count value above 0.5 with an r-table of 0.195 so that the instrument has high validity. The reliability test with Cronbach's Alpha resulted in a value of 0.972 so that the instrument is highly reliable. Exploratory factor analysis also resulted in the finding that the inventory items developed were formed by three factors namely crystallization of vocational preferences, specification of occupational choices, and actualization of occupational choices.